HARMONIZATION OF PROFESSIONAL COMPETENCES IN THE INLAND WATER TRANSPORT (Perner's Contacts, 2019)
The lack of skilled labor is one of the greatest threats to the sustainability and development of inland waterway transport. Currently, there is a necessity for coordinated efforts by all stakeholders of the industry, the European Community, River Commissions, the Member States and other responsible parties. Simplifying and harmonizing legislation on competences, education and skills, including their mutual recognition through the adoption of Directive (EU) 2017/2397, can be a further step in the process of improving the mobility and attractiveness of inland waterway transport.
Keywords: professional competency; competence; water transport; qualification